2018
DOI: 10.1021/acs.biochem.8b00858
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting APOBEC3 Activity with Single-Stranded DNA Containing 2′-Deoxyzebularine Analogues

Abstract: APOBEC3 enzymes form part of the innate immune system by deaminating cytosine to uracil in single-stranded DNA (ssDNA) and thereby preventing the spread of pathogenic genetic information. However, APOBEC mutagenesis is also exploited by viruses and cancer cells to increase rates of evolution, escape adaptive immune responses, and resist drugs. This raises the possibility of APOBEC3 inhibition as a strategy for augmenting existing antiviral and anticancer therapies. Here we show that, upon incorporation into sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
109
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 37 publications
(121 citation statements)
references
References 55 publications
8
109
1
Order By: Relevance
“…On the other hand, inhibition of A3B CTD ‐AL1 by 5FdZ‐oligo was more powerful than that by dZ‐oligo under identical conditions. Previously, we had confirmed that dZ‐oligo is a competitive inhibitor of this enzyme . By monitoring the reaction in the presence of inhibitor at various concentrations, we obtained the inhibition constant ( K i ) for 5FdZ‐oligo [(2.1±0.8) μ m , Supporting Information]; this was 3.5 times lower than the K i of dZ‐oligo [(7.5±1.7) μ m ].…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…On the other hand, inhibition of A3B CTD ‐AL1 by 5FdZ‐oligo was more powerful than that by dZ‐oligo under identical conditions. Previously, we had confirmed that dZ‐oligo is a competitive inhibitor of this enzyme . By monitoring the reaction in the presence of inhibitor at various concentrations, we obtained the inhibition constant ( K i ) for 5FdZ‐oligo [(2.1±0.8) μ m , Supporting Information]; this was 3.5 times lower than the K i of dZ‐oligo [(7.5±1.7) μ m ].…”
Section: Resultsmentioning
confidence: 93%
“…To assess the inhibition of A3 enzymes directly, we used a previously described NMR‐based activity assay in which the DNA substrate deamination is monitored by 1 H NMR spectroscopy in the presence of enzyme with and without inhibitors . The NMR‐based inhibition assay is a direct assay using just A3 enzymes; it does not require a secondary enzyme, such as uracil‐DNA glycosylase (UDG), as used in many indirect assays.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations